Fishing, North Coast, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
Depicts a fisherman fishing off a rock somewhere along the rugged north coast of Trinidad. Postcard number 88370.
Colour: Coloured; Style: Portrait; Other: Bordered; Divided; Replica of painting
Keywords: Postcards; Trinidad and Tobago; Fishing--Trinidad and Tobago; Coasts--Trinidad and Tobago; Fishers--Trinidad and Tobago